Dynamic intron retention modulates gene expression in the monocytic differentiation pathway. Issue 2 (12th December 2021) - Song, Renhua; Tikoo, Shweta; Jain, Rohit; Pinello, Natalia; Au, Amy Y. M.; Nagarajah, Rajini; Porse, Bo; Rasko, John E. J.; J.‐L. Wong, Justin
Abstract: Monocytes play a crucial role in maintaining homeostasis and mediating a successful innate immune response. They also act as central players in diverse pathological conditions, thus making them an attractive therapeutic target. Within the bone marrow, monocytes arise from a committed precursor termed Common Monocyte Progenitor (cMoP). However, molecular mechanisms that regulate the differentiation of cMoP to various monocytic subsets remain unclear. Herein, we purified murine myeloid precursors for deep poly‐A‐enriched RNA sequencing to understand the role of alternative splicing in the development and differentiation of monocytes under homeostasis. Our analyses revealed intron retention to be the major alternative splicing mechanism involved in the monocyte differentiation cascade, especially in the differentiation of Ly6C hi monocytes to Ly6C lo monocytes. Furthermore, we found that the intron retention of key genes involved in the differentiation of murine Ly6C hi to Ly6C lo monocytes was also conserved in humans. Our data highlight the unique role of intron retention in the regulation of the monocytic differentiation pathway. Abstract : We identify intron retention as a major alternative splicing mechanism that fine‐tunes the expression of key genes in the monocytic differentiation pathway. Our analysis shows conservation of intron retention events involved in the differentiation of Ly6C hi monocytes to Ly6C lo monocytes in both mouse and human.